Baicalin attenuates XRCC1-mediated DNA repair to enhance the sensitivity of lung cancer cells to cisplatin. (4th May 2022) - Yin, Zhangyong; Chen, Enguo; Cai, Xiaoping; Gong, Enhui; Li, Yuling; Xu, Cunlai; Ye, Zaiting; Cao, Zhuo; Pan, Jiongwei
Abstract: Baicalin plays important roles in different types of cancer. A previous report showed that baicalin attenuates cisplatin resistance in lung cancer. However, its mechanism remains unclear. In this study, we investigated the effect and mechanism of baicalin on DNA repair and sensitivity of lung cancer cells to cisplatin. A549 and A549/DPP cells were treated with baicalin and cisplatin. A549/DPP cells were transfected with XRCC1 and siXRCC1. Cell viability and DNA damage were detected by MTT and comet assay. Apoptosis rate and cell cycle were detected by flow cytometry assay. The expressions of Bax, Bcl-2, and Cyclin D1 were detected by western blot. XRCC1 expression was detected by reverse transcription quantitative polymerase chain reaction (RT-qPCR) and western blot. Baicalin and cisplatin decreased cell viability in A549 and A549/DPP cells in dose-dependent manner. Baicalin enhanced the effect of cisplatin on promoting apoptosis, arresting cell on S stage and triggering DNA damage accompanied with the upregulation of Bcl-2-associated X protein (Bax) and downregulation of B-cell lymphoma 2 (Bcl-2) and Cyclin D1 in A549/DPP cells. Moreover, baicalin promoted the inhibitory effect of cisplatin on XRCC1 expression in A549 and A549/DPP cells. However, the synthetic effects of baicalin and cisplatin on A549/DPP cells were partially inhibited by XRCC1 overexpression and promoted by XRCC1 knockdown. This study demonstrates that baicalin interferes with XRCC1-mediated cellar DNA repair to sensitize lung cancer cells to cisplatin.